2004
DOI: 10.1203/01.pdr.0000110524.88784.dd
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α, Sexual Dimorphism and Reduced-Size Liver Ischemia and Reperfusion Injury in Mice

Abstract: Estrogen (E 2 ) exerts its effect on target organs principally by interacting with specific estrogen receptors (ER) such as ER-␣ or ER-␤. The role that these E 2 receptors play in mediating the protective effects observed in RSLϩI/R induced injury remains to be defined. To study the role of ER-␣, we anesthetized female and male wild type (wt; C57Bl/6) and ER-␣-deficient (␣ERKO) mice and subjected them to 70% liver ischemia for 45 min followed by resection of the remaining 30% nonischemic lobes and reperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Variables previously shown to affect performance in response to hepatic IRI are animal sex (Harada et al 2004) strain (Burne et al 2000, Shireman & Quinones 2005, Dodd et al 2006) and intraoperative temperature regulation (Biberthaler et al 2001, Kato et al 2002, Khandoga et al 2003. These factors have been tested in heterogeous models of hepatic IRI, and as a result, experiments cannot be directly compared; their results are difficult to apply directly to the development of new experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Variables previously shown to affect performance in response to hepatic IRI are animal sex (Harada et al 2004) strain (Burne et al 2000, Shireman & Quinones 2005, Dodd et al 2006) and intraoperative temperature regulation (Biberthaler et al 2001, Kato et al 2002, Khandoga et al 2003. These factors have been tested in heterogeous models of hepatic IRI, and as a result, experiments cannot be directly compared; their results are difficult to apply directly to the development of new experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, estrogen receptor α is the principally expressed form, and estrogen receptor β is expressed at only low levels (Kuiper et al, 1997). Estrogen-treated mice are reportedly protected from the injurious effects of hepatic ischemia and reperfusion, and estrogen protected mice from diethylnitrosamine-induced hepatocarcinogenesis (Harada et al, 2004;Naugler et al, 2007). These results suggest that estrogen plays a protective role in the pathology of hepatotoxicity.…”
Section: Introductionmentioning
confidence: 90%
“…There are two estrogen receptors (ERs), ER-a and ER-b, which are differentially expressed in different tissues [21]. A recent study reported that ER-a may be involved in the reduction of liver ischemia and reperfusion injury in mice [22]. Although E2 administration ameliorates hepatic injury following trauma-hemorrhage, it remains unknown which subtype of ER is predominantly responsible for the salutary effects of E2.…”
Section: Introductionmentioning
confidence: 99%